2013
DOI: 10.11634/233028791301386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motivation on Job Performance by Community Development Workers in Osun State, Nigeria

Abstract: The study determined the effect of motivation on job performance of community development workers contributing to sustainable rural infrastructural development in Osun State. Specifically, it examined motivational packages provided for the workers, determined the extent to which selected socio-economics characteristics affect their job performance. Samples of 240 community development workers were interviewed. Structured questionnaire dully pre-tested for validity was used to collect primary data. Frequency co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…A study conducted in Nigeria, based on community Development workers, found that the rate of job performance is depend on the level of motivational package given to them. Because of this significant relationship between motivation and performance, it is recommended that the organizations should increase the motivational reward in order to enhance job performance of employees (Olalere, 2015). Another study conducted in Nigeria by based on library staff, has found that there is a positive and significant correlation and relationship between employees work performance and motivational strategies.…”
Section: Impact Of Employee Motivation On Job Performancementioning
confidence: 99%
“…A study conducted in Nigeria, based on community Development workers, found that the rate of job performance is depend on the level of motivational package given to them. Because of this significant relationship between motivation and performance, it is recommended that the organizations should increase the motivational reward in order to enhance job performance of employees (Olalere, 2015). Another study conducted in Nigeria by based on library staff, has found that there is a positive and significant correlation and relationship between employees work performance and motivational strategies.…”
Section: Impact Of Employee Motivation On Job Performancementioning
confidence: 99%
“…The occupational hazards prevalence was measured using a 9-item questionnaire. Agricultural workers' job performance was measured by adapting an 11-item scale of Adisa (2013). The respondents expressed their degree of agreement on a 5-point rating scale ranging from Strongly Agree to Strongly Disagree.…”
Section: Methodsmentioning
confidence: 99%
“…The objectives of the study were brief and explained to all respondents. Data was collected face-to-face interview using questionnaire adopted and adapted from Chatio [ 27 ] and Adisa [ 28 ]. The questionnaire consists of five sections: sociodemographic profile (7 questions); motivation (5 questions); organization input (9 questions); knowledge (10 questions); and role performance (7 questions).…”
Section: Methodsmentioning
confidence: 99%